Requirements for the application of the Kaizen strategy in management for the purpose of improving administrative processes from the point of view of the administrative stuff (Field study on the College of Education for Girls in Shaqraa) - Al-Kasr, Sherifa bint Awad (Journal of Economic, Administrative and Legal Sciences, 2017)
The purpose of this scientific paper was know the views of members of the governing body of the Faculty of Girls' Education collage at Shaqra University in the importance of the requirements of kaizen strategy in management at collage, and the possibility of the application of these requirements at this collage. To address the problem of the research used a descriptive approach, and data for the study were collected through survey questioners were distributed to a sample of members of the governing body in the College of Education at Shaqra University. It was the use of the following statistical methods: percentages and averages, standard deviation. Search Results showed that the importance of the requirements of the management strategy kaizen got high esteem among the members of the governing body of the answers. The results also revealed that the possibility of the application of the requirements of the strategy got a median estimate. By the end, presented research proposals, including that Shaqra University to adopt a strategy in Kaizen management as a tool of change and development of the administrative work.
Keywords: higher education; management; strategy kaizen; members of the governing body